Too much of a good thing? When empathy becomes associated with depression and anxiety in women - Hannah L. Belcher; Rachel van Marle; Ruth Ford; Sharon Morein-Zamir (Psychiatry Research Communications)
Previous research has suggested that increased empathy is associated with improved wellbeing, however, other research has also suggested that too much empathy is associated with heightened levels of anxiety and depression. This is particularly the case for women, with elevated empathy being linked with some female-biased psychiatric conditions. The current study aimed to clarify these contradictory findings by assessing the association between different empathy levels on the Empathy Quotient and psychiatric diagnoses quadratically, rather than just linearly. 2998 women completed an online questionnaire measuring empathy and diagnoses of common psychiatric conditions. Logistic regression analyses for diagnoses of depression and anxiety indicated that in both EQ scores had significant quadratic relationships albeit with small effect sizes. The frequency of depression and anxiety diagnoses was generally lower the higher the empathy, but cases rose for the highest levels of empathy. This indicates that while empathy is largely a positive trait, very high levels of empathy are a risk factor for diagnoses of depression and anxiety. These findings clarify prior inconsistencies in the literature and point to the importance of investigating non-linear relationships between key psychological constructs and mental health.